2011
DOI: 10.1002/maco.201005871
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the oxide scale formation on Fe‐Cr steel during exposure in liquid lead‐bismuth eutectic in the 450–600 °C temperature range

Abstract: Previous studies showed that the oxidation of T91 (Fe-9Cr martensitic steel) in liquid Pb-Bi eutectic leads to the formation of a duplex oxide layer containing an inner Fe 2.3 Cr 0.7 O 4 spinel layer and an upper magnetite layer. The magnetite layer is easily removed by the Pb-Bi flow when the oxygen concentration is low and the flow velocity is high. This phenomenon is not currently understood. The magnetite layer growth rate is limited by the iron diffusion in the oxide layer lattice. The Fe-Cr spinel layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 37 publications
3
17
0
2
Order By: Relevance
“…1 Comparison between the simulated total oxide thicknesses and the observed oxide thicknesses formed after corrosion tests on ground polished T91 at 1 atm and 250 bars magnetite layer was removed, the kinetics of oxide growth was not accelerated. From this result, they concluded that it was the iron diffusion through the inner FeCr spinel oxide lattice which was the rate limiting process at 470°C in lead bismuth [7]. Surman et al [15] proposed the same rate limiting oxide layer for mild steel and low alloy steel oxidation in CO 2 without demonstrating it clearly.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…1 Comparison between the simulated total oxide thicknesses and the observed oxide thicknesses formed after corrosion tests on ground polished T91 at 1 atm and 250 bars magnetite layer was removed, the kinetics of oxide growth was not accelerated. From this result, they concluded that it was the iron diffusion through the inner FeCr spinel oxide lattice which was the rate limiting process at 470°C in lead bismuth [7]. Surman et al [15] proposed the same rate limiting oxide layer for mild steel and low alloy steel oxidation in CO 2 without demonstrating it clearly.…”
Section: Resultsmentioning
confidence: 93%
“…Martinelli et al [7] have reported an extensive study of the expression of the iron diffusion coefficient in magnetite and Fe 2.3 Cr 0.7 O 4 from literature data [8][9][10]. They concluded that the expression of the iron diffusion coefficient in magnetite D Fe M at intermediate temperature can be written as:…”
Section: Simulation Methodologymentioning
confidence: 96%
See 2 more Smart Citations
“…Magnetitová vrstva roste difúzí železa až do rozhraní PbBi/oxid, zatímco spinelová vrstva Fe-Cr roste na rozhraní kov/oxid uvnitř prostoru. Mezním mechanismem procesu tvorby ochranné vrstvy je difúze, která umožňuje vytvoření prostoru pro růst spinelu Fe-Cr [6,7,9]. Podle těchto předpokladů závisí tloušťka oxidické vrstvy spinelu Fe-Cr od schopnosti tvorby magnetitu, která je také závislá na obsahu kyslíku v prostředí a na mikrostruktuře povrchové vrstvy.…”
Section: Diskuzeunclassified